Factors Affecting Patient's Length of Stay In The Era Of Covid-19 Pandemic In Emergency Room Persada Hospital - Simanungkalit, Sylvia Kitty; Holipah, Holipah; Dewanto, Aryo; David, David (Fakultas Kedokteran Universitas Brawijaya)
Length of stay (LOS) of a patient in an Emergency Room (ER) is the interval between the time the patient arrives and the time the patient physically leaves the ER. Prolonged LOS has potential to cause crowding. Meanwhile, from a clinical point of view, the factor of LOS has an impact on service suspension, which can reduce patient safety, even to death. Covid-19 pandemic has made hospitals establish a strict patient screening system and has the potential to increase the LOS of patients in the ER. The purpose of this study was to identify the factors that contribute to the LOS of patients. This study is an observational study of 38 respondents who came to the Emergency. LOS was compared between before and during Covid-19 pandemic condition. Observations were carried out by the Time Motion Study method to determine the patient's average time at each stage of the ER. The results showed the average LOS for emergency room patients with inpatient plans was 2 hours 7 minutes, while the LOS during pandemic was 4 hours 46 minutes 52 seconds. There were 2 hours 39 minutes 52 seconds time extension. The time extension is due to several factors: results of laboratory tests SARS COV-2; approval process for the Covid-19 Screening Team; Emergency Room and Laboratory were located in separate buildings.